# Lim X → ∞ { X 2 + 2 X + 3 2 X 2 + X + 5 } 3 X − 2 3 X + 2 - Mathematics

$\lim_{x \to \infty} \left\{ \frac{x^2 + 2x + 3}{2 x^2 + x + 5} \right\}^\frac{3x - 2}{3x + 2}$

#### Solution

$\lim_{x \to \infty} \left( \frac{x^2 + 2x + 3}{2 x^2 + x + 5} \right)^\left( \frac{3x - 2}{3x + 2} \right)$
$= \lim_{x \to \infty} \left[ 1 + \frac{x^2 + 2x + 3}{2 x^2 + x + 5} - 1 \right]\left( {}^\frac{3x - 2}{3x + 2} \right)$
$= \lim_{x \to \infty} \left[ 1 + \frac{\left( x^2 + 2x + 3 \right) - \left( 2 x^2 + x + 5 \right)}{2 x^2 + x + 5} \right]^\left( \frac{3x - 2}{3x + 2} \right)$
$= \lim_{x \to \infty} \left[ 1 + \frac{\left( - x^2 + x - 2 \right)}{2 x^2 + x + 5} \right]^\left( \frac{3x - 2}{3x + 2} \right)$
$= e^\lim_{x \to \infty} \left( \frac{- x^2 + x - 2}{2 x^2 + x + 5} \right) \times \left( \frac{3x - 2}{3x + 2} \right)$
$= e^\lim_{x \to \infty} \left( \frac{- 1 + \frac{1}{x} - \frac{2}{x^2}}{2 + \frac{1}{x} + \frac{5}{x^2}} \right) \times \left( \frac{3 - \frac{2}{x}}{3 + \frac{2}{x}} \right)$
$= e^{- \frac{1}{2} \times 1}$
$= \frac{1}{\sqrt{e}}$


Is there an error in this question or solution?

#### APPEARS IN

RD Sharma Class 11 Mathematics Textbook
Chapter 29 Limits
Exercise 29.11 | Q 6 | Page 77